DETERMINANT FACTORS IN PREDICTING MUSLIM FASHION PURCHASE DECISION: A CASE IN NEW ENTRANTS BUSINESS - Jannah, Kenanga Miftakhul; Puspita, Rosana Eri; Mochlasin, Mochlasin (Al-Infaq: Jurnal Ekonomi Islam, 2022)
This study aims to determine the effect of price, product, promotion, and Islamic business ethics on purchasing decisions in new entrants' Muslim fashion businesses with intentionto-buy as an intervening variable. The indicators used are prices regarding prices, purchasing power, competitiveness, and price comparisons. Data processing is carried out through a quantitative approach with primary data collected through questionnaires with the following techniques simple random sampling with a sample of 90 respondents. Data analysis using SPSS application. Based on research results, it was found that price, product, promotion, and Islamic business ethics have significant positive effects on purchasing decisions and intention to buy. As for the price and Islamic business ethics,significant positive effects on purchasing decisions by mediating buying intention, products, and promotions have a significant negative effect on purchasing decisions and cannot be mediated intention to buy. New entrants Muslim fashion businesses must make improvements from each of the determinants of the purchase decision to increase the existence to be more popular.